# Rearranging Formula

Watch
Announcements
#1
Make g the subject of g-1= gh+3h
can someone help me with this question s
thanks
0
3 years ago
#2
You're probably going to need to factorise
0
3 years ago
#3
Collecting g terms on one side and factorising is usually the best way to go.

Spoiler:
Show

0
3 years ago
#4
g - 1 = gh + 3h
- 1 - 3h = gh - g
- 1 - 3h = g(h-1)
(Divide both sides by h -1)
- 1 - 3h/h-1 = g

Is this right?
0
3 years ago
#5
-1=gh+3h-g
-1-3h=gh-g
-1-3h=g(h-1)
g=(-1-3h)/(h-1)
0
#6
Thanks Guys !
0
#7
yeah u are right !
(Original post by thrifty_reviser)
g - 1 = gh + 3h
- 1 - 3h = gh - g
- 1 - 3h = g(h-1)
(Divide both sides by h -1)
- 1 - 3h/h-1 = g

Is this right?
0
3 years ago
#8
I know you've already got the answer, but I might as well practise for my maths exam tomorrow!

Spoiler:
Show

g-1=gh+3h
g=gh+3h+1
g-gh=3h+1
g(1-h)=3h+1

g = (3h+1)/(1-h)
0
X

new posts
Back
to top
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### Poll

Join the discussion

Yes (60)
29.27%
No (145)
70.73%